2013
DOI: 10.1002/jbm.b.32853
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene oxide's role as a reactive agent during sterilization: Effects of polymer composition and device architecture

Abstract: Sterilization conditions need to be optimized to effectively neutralize the bioburden while using short exposure times for minimizing the changes in chemical composition, material properties and device architecture. Towards this goal, effects of ethylene oxide (EtO) exposure parameters such as time, temperature, humidity, and EtO concentration on the polymer properties were investigated by monitoring the changes in composition, and the morphology of different types of structures in a family of poly(ethylene gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 15 publications
1
33
0
1
Order By: Relevance
“…12 EtO alters scaffold properties by penetrating into polymeric networks and reacting with chemical groups. 13 Given the translational nature of tissue-engineering research and constant innovation in polymer systems and their processing technologies, the issue of sterilization needs to be periodically revisited. In this study, we systematically explore the feasibility of using peracetic acid (PAA) as a chemical sterilant for polymeric tissue-engineered scaffolds and compared it with two accepted methods of sterilization (EtO and autoclaving) and a high-level disinfectant (80% ethanol).…”
Section: Introductionmentioning
confidence: 99%
“…12 EtO alters scaffold properties by penetrating into polymeric networks and reacting with chemical groups. 13 Given the translational nature of tissue-engineering research and constant innovation in polymer systems and their processing technologies, the issue of sterilization needs to be periodically revisited. In this study, we systematically explore the feasibility of using peracetic acid (PAA) as a chemical sterilant for polymeric tissue-engineered scaffolds and compared it with two accepted methods of sterilization (EtO and autoclaving) and a high-level disinfectant (80% ethanol).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ethylene oxide can react with amide, carboxyl, and carbonate functional groups on polymer chains, which could also impact drug release from polymeric scaffolds. 39 In fact, Phillip et al demonstrated esterification of PLGA samples following EtO treatment, which could also be a mechanism of the attenuated burst release observed in this study. 39 Philip et al also displayed enhanced smoothing on the surface of PLGA implants treated with EtO indicating that total surface area involved in hydrolytic degradation could be a factor involved in the delayed burst release observed in our EtOsterilized groups.…”
Section: ■ Discussionmentioning
confidence: 76%
“…39 In fact, Phillip et al demonstrated esterification of PLGA samples following EtO treatment, which could also be a mechanism of the attenuated burst release observed in this study. 39 Philip et al also displayed enhanced smoothing on the surface of PLGA implants treated with EtO indicating that total surface area involved in hydrolytic degradation could be a factor involved in the delayed burst release observed in our EtOsterilized groups. 39 Other authors have also demonstrated that EtO sterilization can alkylate amines and decrease protein functionality, thus it is possible that the slightly decreased bioactivity in EtO implants observed in this study is due to a decrease in functional protein at the surface of the microspheres.…”
Section: ■ Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although one study 14 has reported that ethylene oxide could change plastic structures, sterilization of plastic materials with ethylene oxide gas is generally accepted as a standard sterilization procedure in healthcare facilities. 10,15 The average VAS score for patient discomfort in our study in the plastic bag group (5.33) was significantly higher than that in the commercially available hygienic sheath group (3.03).…”
Section: Discussionmentioning
confidence: 99%